2014
DOI: 10.1021/cm5031415
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Voltage-Fade Mechanism in High-Energy-Density Lithium-Ion Batteries: Origin of the Tetrahedral Cations for Spinel Conversion

Abstract: High-voltage layered lithium- and manganese-rich (LMR) oxides have the potential to dramatically enhance the energy density of current Li-ion energy storage systems. However, these materials are currently not used commonly; one reason is their inability to maintain a consistent voltage profile (voltage fade) during electrochemical cycling. This report rationalizes the cause of this voltage fade by providing evidence of layered to spinel (LS) structural evolution pathways in the host Li1.2Mn0.55Ni0.15Co0.1O2 ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
227
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 268 publications
(235 citation statements)
references
References 29 publications
4
227
1
3
Order By: Relevance
“…16,21 Their in operando X-ray diffraction measurements reveal an increase in c-and decrease in a-lattice parameters leading to a gradual non-monotonic decrease in unit cell volume during the first charge to 4.8 V. The observed crystal structure changes do not correlate exactly with the measured stress, which indicates that the supposedly 'inactive' electrode components such as the carbons and the binder also contribute to stress evolution. For instance, intercalation of PF 6 − anions at voltages >4.45 V vs. Li/Li + leads to lattice expansion and structure disordering of graphite contained in the positive electrode. 22 In addition, the maximum stress, between 1.2 and 1.5 MPa, displayed by the positive electrode could also be due to the finite tensile strength of the PVdF binder.…”
Section: Resultsmentioning
confidence: 99%
“…16,21 Their in operando X-ray diffraction measurements reveal an increase in c-and decrease in a-lattice parameters leading to a gradual non-monotonic decrease in unit cell volume during the first charge to 4.8 V. The observed crystal structure changes do not correlate exactly with the measured stress, which indicates that the supposedly 'inactive' electrode components such as the carbons and the binder also contribute to stress evolution. For instance, intercalation of PF 6 − anions at voltages >4.45 V vs. Li/Li + leads to lattice expansion and structure disordering of graphite contained in the positive electrode. 22 In addition, the maximum stress, between 1.2 and 1.5 MPa, displayed by the positive electrode could also be due to the finite tensile strength of the PVdF binder.…”
Section: Resultsmentioning
confidence: 99%
“…122 The voltage fade has been attributed to chemical and structural changes including oxygen evolution, Ni and Co migration from the surface into the bulk, reduction of Mn 4+ to Mn 3+ , and formation of a spinel-like phase. [123][124][125][126][127][128][129] The spinel-like phase is formed by the migration of lithium ion from octahedral lithium site to tetrahedral lithium site and migration of TM ions from octahedral M site to octahedral lithium site via oxygen vacancies. Therefore, strategies to mitigate phase change are to restrict the cation migration.…”
Section: High-voltage Cathode Materialsmentioning
confidence: 99%
“…The phase change also results in a somewhat more complex CEI formation mechanism than that of Ni-rich NMC. 130,131 Strategies to stabilize the surface of Li-rich NMCs include coatings, [132][133][134][135] surface treatments, 126 cycling protocols, 136 synthesis routes, 137,138 and electrolyte additives. 135 Most of these efforts have failed to stop the underlying mechanisms responsible for voltage fade, 135 although compositions that incorporate small amounts of spinel domains into the layered structure show some promise.…”
Section: High-voltage Cathode Materialsmentioning
confidence: 99%
“…10 Further studies have also been widely done to unravel the mechanism underlying the intrinsic voltage decay upon subsequent cycling of Li-rich manganese layered oxide. [11][12][13][14] Recently, we first reported that the solid solution of Li 2 Mn 1¹x Ru x O 3 exhibit high capacity of about 200 mAh g ¹1 and lower electrical resistivity five order of magnitude than Li 2 MnO 3 , indicating that the substitution of Ru is effective to enhance the electrochemical as well as electrical properties. 15 Li 2 RuO 3 is isostructural with Li 2 MnO 3 , composed of lithium and lithium-transition metal layer except for a minor stacking difference.…”
Section: Introductionmentioning
confidence: 99%